2015
DOI: 10.1134/s1028335815050055
|View full text |Cite
|
Sign up to set email alerts
|

The geomechanics of gas recovery from coal seams

Abstract: In connection with the depletion of large and avail able deposits of hydrocarbon raw materials, the devel opment of nontraditional sources acquires increas ingly larger topicality. Methane, which is contained in gas saturated coal seams, is a promising local energy source and high quality and environmentally pure energy carrier.The main problem of recovery of methane from coal seams is the low natural permeability of the coal massif [1]. To increase the permeability, a system of fil tration channels should be … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 4 publications
0
3
0
Order By: Relevance
“…Finally using the Eqs. (26), (29) and (30), we get the following differential equation in terms of u(ϕ) as follows…”
Section: B Geodesic Equationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally using the Eqs. (26), (29) and (30), we get the following differential equation in terms of u(ϕ) as follows…”
Section: B Geodesic Equationsmentioning
confidence: 99%
“…The study of light bending when calculated based on the first order expansion of the smallest deflection angle, it is then called weak gravitational lensing (WGL). A number of applications on WGL came through observational cosmology and technical advances in [29][30][31][32][33]. Their quantitative analysis provides specific distribution and evolution of matter.…”
Section: Introductionmentioning
confidence: 99%
“…Other studies have been led by Klimov, Liebes, refsdal and Bourassa and Kantowski [2]. Klimov investigated the lensing of galaxies by galaxies [3], but Liebes studied the lensing of stars by stars and also stars by clusters in our galaxy [4]. Refsdal showed that the geometrical optics can be used for investigating the gravitational lenses properties and time delay resulting from it [5,6].…”
Section: Introductionmentioning
confidence: 99%